(3GdBdI GdQUOjI GdeSeGI HPGJ GdcQSjs - (3eMeO Hf Ydj GdMejOj GdQhej GdMfaj,J (B1179 (3g` s ((3eMeO Hf eMeO GdNGdOi GdhOZjQi GdMSfi s)
(3ChdgG (B:s
(3fMeOc jGef jOhQ Gdadc hHYO , ajbhd deG cGfJ PGJ GdcQSi ef GdBdGJ GdQUOjI cKjQI GdeMUhd , jSjQI GdMUhd , heY gPG eJQhcI GdYed ai GdHdGO s
(3BNQgG (B:s
(3gh eWGdY GdhbJ , hEf TFJ aRO GdeGVi ef GdfgGQ Ydi eWGdY GdTQhb, ChQO GdeGVi ef Gddjd Ydi eWGdY GdZQhH , aGdMGUd gh GdeWdhH hdjcf gPG BNQ eG ChQOfGg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3jJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs